Membrane-like structure in the urinary bladder neck of a young cat: diagnosis and treatment using balloon dilatation and a balloon-expandable metallic stent. Issue 2 (October 2017) - Ruiz-Drebing, Matias; Yap, Fui; Seth, Mayank; Dennis, Ruth; Dominguez, Elisabet
Case summary: A 33-month-old, spayed female domestic shorthair cat was referred to the Animal Health Trust for the investigation of urinary incontinence and straining to urinate. A membrane-like structure was detected in the bladder neck, which caused partial obstruction of the urinary bladder. A combination of different imaging techniques, including ultrasonography, radiography, CT and fluoroscopy, was essential in the diagnosis, surgical planning and treatment of this intravesicular stricture. During retrograde vaginourethrocystogram, unexpected subcapsular accumulation of contrast medium was seen around both kidneys on radiographs and confirmed with CT. Three different treatments were performed, including surgical debridement, balloon dilatation and placement of a self-expanding metallic stent across the stricture. Histopathology of the membrane was unable to differentiate whether the lesion was congenital or acquired. No urinary incontinence was observed 5 months after placement of the metallic stent. Relevance and novel information: This is the first reported case using fluoroscopic-guided balloon dilatation of the bladder neck for the treatment of a bladder neck stricture. Presence of renal subcapsular contrast medium secondary to a retrograde vaginourethrocystogram due to partial obstruction at the bladder neck in a cat has not been previously described.